Multiple Regression Analysis of Factors Affecting the Mental Component Score Constituents of SF-36 in Adult Spinal Deformity. Issue 1 (April 2016) - Ayhan, Selim; Yuksel, Selcem; Niyazi, Asli; Nabiyev, Vugar; Güler, Ümit Özgür; Mmopelwa, Tiro; Sabat, Montse Domingo; Pellise, Ferran; Alanay, Ahmet; Perez-Grueso, Francisco Javier Sanchez; Kleinstuck, Frank; Obeid, Ibrahim; et al.
Introduction: As surgical decision-making and preoperative planning for adult spinal deformity (ASD) need strongly be interrelated to health related quality of life (HRQOL), there are multiple studies focusing on factors with an impact on it. Based on the general perception of association between the treatment results and the psychological condition of patients with ASD, analyzing the factors governing the baseline psychological status of this group may be worthwhile. Aim of study is to develop an understanding of which factors have a greater impact on the SF-36 mental component score (MCS) and to establish a hierarchy of these parameters through multiple regression analysis. Material and Methods: Prospectively collected data from a multicentric adult deformity database was analyzed using multiple regression analysis with SF-36 MCS designated as the dependent variable and demographic, radiological and the HRQOL parameters as independent variables. The regression model was started with a correlation analysis between SF-36 MCS and all independent variables then conducted by introducing the variables with the highest correlation with SF-36 MCS, sequentially. Results: A total of 229 patients (181♀, 47♂) with a mean age of 49.4 (18– 85) years, were analyzed. A strong correlation between SF-36 MCS and Scoliosis Research Society (SRS)-22, Oswestry Disability Index (ODI), gender, and diagnosis were found ( p < 0.05). The distribution graph and results of regression analysis are summarized in Fig. 1. The overall R2 of this model was 0.254 ( p < 0.001). Conclusion: This study has demonstrated that, among the evaluated parameters, the overall HRQOL (SRS-22 and ODI) as well as thoracic kyphosis (TK) and gender are the most important parameters affecting the mental component summary of SF-36 in ASD population. Although the strong association with SRS-22 and/or ODI was to be expected, less strong associations with TK (as a token of appearance?) and gender (due to different mechanisms of coping with disability?) were less expected and may warrant further consideration in our understanding of the population of ASD.